Wastewater treatment by reverse osmosis process : state of the art & process modelling - Al-Obaidi, Mudhar; Kara-Zaitri, Chakib; Mujtaba, I. M. (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"Wastewater treatment by reverse osmosis process : State of the art and process modelling is part of a two-volume set that provides a one-stop-shop for reverse osmosis (RO), outlining its scope and limitations for the removal of organic compounds from wastewater. This volume covers the state-of-the-art on RO processes and describes ten RO process models of different features and complexities. This work is an invaluable resource for engineers and scientists working within the field of wastewater treatment"--
OCLC-licensed vendor bibliographic record.
Keywords: Sewage -- Purification -- Reverse osmosis process; SCIENCE / Biotechnology; TECHNOLOGY / Engineering / Chemical & Biochemical